Spaces of Empathy: Visual Strategies in Photojournalistic Imagery of Migration - Nilsson, Maria (Imaginations)

(untitled) (York University, 2022)
This essay explores visual representations of migration by drawing on a Swedish case to reflect on broader questions regarding the position of the witness, including the photographer and the distant spectator, and on how photographs may contribute to an understanding of the experience of forced migration. Through an interpretative analysis of imagery recognized by the Swedish Picture of the Year contest, I identified mostly empathetic visualizations, according to the five positions of visibility suggested by Chouliaraki and Stolic. Engaging a different set of imagery, I delved into an extended exploration of one family over a span of four years as a narrative of lived experiences of forced migration. Methodologically, this essay begins within the area of photojournalism, but suggests the inclusion of varied visual forms and genres in the empirical materials.